2021
DOI: 10.1159/000520272
|View full text |Cite
|
Sign up to set email alerts
|

Positioning Aeromonas Infection in Inflammatory Bowel Disease: A Retrospective Analysis

Abstract: Background and Aim: Aeromonas are Gram-negative rods known to cause a spectrum of diseases. Inflammatory bowel disease (IBD) is an idiopathic complex condition resulting from interaction of multiple factors. Aeromonas infection in association with IBD is still largely unknown. We aim to look for the significance of Aeromonas infection and for significant differences between IBD and non-IBD patients. Methods: A retrospective observational analysis was performed of all patients positive for Aeromonas in stool cu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(6 citation statements)
references
References 22 publications
1
2
0
Order By: Relevance
“…By implementing such screening measures, targeted antibiotic intervention can be promptly provided. This viewpoint is further supported by previous clinical studies, which showed that patients with IBD infected with Aeromonas experienced more complications and required more frequent antibiotic treatment as compared to non-IBD patients ( 7 , 8 ).…”
Section: Discussionsupporting
confidence: 73%
See 1 more Smart Citation
“…By implementing such screening measures, targeted antibiotic intervention can be promptly provided. This viewpoint is further supported by previous clinical studies, which showed that patients with IBD infected with Aeromonas experienced more complications and required more frequent antibiotic treatment as compared to non-IBD patients ( 7 , 8 ).…”
Section: Discussionsupporting
confidence: 73%
“…Previous studies have examined the clinical presentations and treatment of Aeromonas enteric infection in patients with IBD ( 7 10 ). For example, studies from Lobaton et al and Guedes et al reported that patients with IBD infected with Aeromonas were treated more often with antibiotics compared to non-IBD patients ( 7 , 8 ).…”
Section: Introductionmentioning
confidence: 99%
“…An increase in the relative abundance of Aeromonas was observed in patients with inflammatory bowel disease, including ulcerative colitis and Crohn’s disease. Its infection symptoms include diarrhea, bleeding, inflammation, and abdominal pain in IBD [ 53 ]. Staphylococcus is a type of pathogenic Gram-positive bacteria with a high detection rate in various inflammatory wounds.…”
Section: Discussionmentioning
confidence: 99%
“…The rates of stool isolation differ depending on factors such as geographical location, dietary habits, and isolation methods. In developed countries, the prevalence of infection ranges from 0.8% to 7.4%, and the carriage rate ranges from 0% to 4% [2]. Although it remains unclear what exactly causes inflammatory bowel disease (IBD), there are numerous factors at play within its network of pathogenic mechanisms, including environmental influences, genetic susceptibility, dysregulated immune responses, and microbiological factors.…”
Section: Discussionmentioning
confidence: 99%
“…The most frequent manifestation of Aeromonas infection is diarrhea, which is typically sudden and resolved on its own. However, there have also been reported cases of bloody diarrhea and abdominal pain, as well as chronic and less severe diarrhea [2]. Different types of Aeromonas species possess various virulence factors, such as cytotoxic and cytotonic toxins, proteases, hemolysins, lipases, adhesins, agglutinins, pili, enterotoxins, and several other enzymes.…”
Section: Introductionmentioning
confidence: 99%